Adenoid Cystic Carcinoma of the Lacrimal Gland in a 36 year Old Male - Edward Paul P ORAIN; - TAN HERNANDEZ; Anne Jo (Journal of Ophthalmic Science, 2023)
A case of lacrimal gland adenoid cystic carcinoma in a 36‑year‑old male is presented. The report reviews imaging, histopathology, perineural invasion risk, and multimodal management including surgery and radiotherapy.
Keywords: Adenoid cystic carcinoma